Tribological Properties of Borided AISI 4140 Steel with the Powder Pack-Boriding Method - Ulutan, Mustafa; Yildirim, M. Mustafa; Celik, Osman N.; Buytoz, Soner (Springer/Plenum Publishers, 2010)
The present study evaluates the tribological properties of boride layers on the surface of AISI 4140 steel, formed using the pack-boriding method. Commercial EKabor(A (R))2 was used as the boronizing agent and the treatment was carried out at 900, 950, 1000, and 1050 A degrees C for 2, 4, and 6 h, respectively. X-ray diffraction (XRD), scanning electron microscopy (SEM), and microhardness tests were used to characterize the phase composition, microstructure, and local hardness, respectively, of the borided steel samples. Block-on-disc tests were used to investigate tribological properties. Abrasive wear tests were carried out using emery paper at a fixed sliding speed and three different loads. Adhesive wear tests were executed against AISI 52100 steel at a fixed load and distance. The coefficient of friction values (COF) of the samples were determined simultaneously during the tests. The weight loss and COF of the borided samples were compared with untreated samples and the results suggest that both wear resistance and friction properties of the AISI 4140 steel improve with boriding.
Keywords: AISI 4140 steel; Pack-boriding; Abrasive wear; Adhesive wear